ANALYSES OF REGULATIONS REGARDING ACCOMMODATION FACILITIES CATEGORISATION IN RURAL TOURISM IN SERBIA - Vukosav, Svetlana; Garača, Vuk; Bradić, Milan (Economics of Agriculture, 2018)
The paper analyze the regulation on categorization of accommodation that relate to accommodation in rural tourism. The main aim of the paper is to estimate the point to which legal and administrative procedures reached in recognizing new forms of accommodation in rural tourism in Serbia as well as the level of compliance of legislation with some of the countries in the region. The results of the research render highly signifcant data on identifcation of roles, goals, procedures and purpose of the categorization aimed at pursuing market trends which is of crucial importance for tourism stakeholders. Moreover, the adjustments to international standards have become the imperative for Serbia to successfully continue the EU accession in this tourism branch as well.